PERTUMBUHAN DAN PRODUKSI Caulerpa lentillifera YANG DIBERI MIKROORGANISME LOKAL (MOL) ECENG GONDOK - Arliani Arliani; Andi Asni; Ilmiah Ilmiah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Caulerpa lentillifera seaweed is a seaweed that has high economic value and is widely loved by people in the country and abroad. However, the production of Caulerpa lentillifera itself has not been sufficient because it is seasonal. Therefore, it is necessary to make efforts to increase the production of Caulerpa sp. by applying fertilizer in its cultivation. This study aims to determine the dosage (MOL) of water hyacinth that can provide the best growth and production as well as to determine the nutritional quality of Caulerpa sp. This study used a Complete Randomized Design (RAL) with 4 treatments and 3 replicates, with each MOL administered; Treatment A (control), Treatment B (5 mL MOL/L water), Treatment C (6 mL MOL/L water), and Treatment D (7 mL MOL/L water). The data was analyzed by the ANOVA Test and continued by the Duncan Test. that the administration of MOL water hyacinth with a dose of 6 mL MOL/L of water was the best dose for the growth, production, and nutritional quality of Caulerpa lentillifera. Water hyacinth in Caulerpa lentillifera can exert markedly different effects on absolute growth, specific growth rate, production, moisture content, protein, crude fat, crude fiber, BETN, and ash. The best treatment is C treatment (6 ml MOL/L water).